Penerapan Program Sekolah Lima Hari Dan Implikasinya Terhadap Pembelajaran PAI Di Madrasah Aliyah Negeri 2 Payakumbuh - Welmawati Welmawati; Jerni Aswana Defin; Fairuzane Reza Nabila (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2023)
The focus of this research is motivated by the Ministry of Education and Culture policy regarding five-day schools, which is a solution to teachers' difficulties in fulfilling their obligation to teach 24 hours per week. The Five Day School Program is an educational innovation that aims to improve the quality of education through the effectiveness and efficiency of using time at school. The aim of this program is to help students divide their time well between academic and non-academic activities, both of which are very necessary for student development, and this policy will have a greater impact on student focus in learning. This research was conducted at MAN 2 Payakumbuh using a qualitative method approach as a procedure that produces qualitative descriptive data. The results of the discussion and data analysis show that the implementation of the five-day school policy at MAN 2 Payakumbuh has both positive and negative impacts.